Inter-Relationship Between Cooking Time and Some Physico Chemical Characteristics in Pigeon Pea (Cajanus cajan) Genotypes - Sethi, Shruti; Samuel, D.V.K; Lal, Krishnan (Journal of Agricultural Engineering, 2008)
Thirteen genotypes of pigeon pea were evaluated for their physical and physico-chemical characteristics, namely, seed size, seed volume, seed density, hydration capacity, hydration index, swelling capacity, swelling index and cooking time. Cooking time of whole pigeon pea pulse ranged between 51 and 63 min indicating a large variation. However, the cooking time of pigeon pea dhal ranged between 19 and 31 min. Correlation coefficients between seed weight and hydration capacity (0.77), seed volume and seed weight (-0.86) and that of swelling capacity and swelling index (0.90) were found to be significant at 1% level. Alinear regression model was also fitted between the cooking time of whole pulse and other parameters under study. The coefficient of determination (R2) was observed as 81%. These inter-relationships amongst variables enable to predict the cooking time of whole pulse for a large number of pigeon pea genotypes.